Effects of Transcranial Direct Current Stimulation on Memory of Elderly People with Mild Cognitive Impairment or Alzheimer's Disease: A Systematic Review. (31st May 2022) - da Silva, Eliclebysson Rodrigo; Rodrigues Menezes, Italo Ramon; Brys, Ivani
Background: Transcranial direct current stimulation (tDCS) is one of the most studied non-invasive neuromodulation techniques, presenting itself as a promising technique for several pathologies, such as cognitive decline. Objectives: The aim of this study was to conduct a systematic review of the effects of tDCS on the memory of elderly people with mild cognitive impairment or Alzheimer's disease, in order to describe the main protocols used, and to investigate the therapeutic effectiveness of this technique. Data Sources and Methods: 869 studies reporting controlled clinical trials were found in the databases PubMed, Web of Science, Lilacs, PsycArticles and Scielo, from which 13 met the expected requirements and were included in the final analysis. Results: There was a great variability in the stimulation protocols used in the studies; and methodological weaknesses were observed, such as absence of sample size calculation, and of information on effect sizes. Positive effects of tDCS were observed only in five studies, and the combination of stimulation and cognitive training did not seem to potentiate the effects of tDCS. Conclusion: Although tDCS can be considered a technique with important therapeutic potential, more studies are needed to understand the acute effects of tDCS on memory of elderly people and the durability of these effects over time. Registration: PROSPERO (CRD-42020200573)